2015
DOI: 10.1111/ajr.12160
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for definitive care: An analysis of elapsed time from decision to surgery or transfer in a rural centre

Abstract: Even in the absence of a strict four-hour rule program and a dedicated emergency surgical unit, main outcome measures appear to be comparatively efficient. However, the duration for transfer of patients is suboptimal because of the lack of established pathways for urgent non-trauma transfer from rural centres and bed availability in tertiary hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Median length of hospital stay was 20 and 13 days for transferred and direct admissions, respectively ( P < 0.001) . There were no significant differences in patient characteristics including age, sex, fracture type and fixation method between groups . A 2014 US study of paediatric burns patients also reported an association between interhospital transfer and increased length of stay independent of the percentage of total body surface area affected …”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Median length of hospital stay was 20 and 13 days for transferred and direct admissions, respectively ( P < 0.001) . There were no significant differences in patient characteristics including age, sex, fracture type and fixation method between groups . A 2014 US study of paediatric burns patients also reported an association between interhospital transfer and increased length of stay independent of the percentage of total body surface area affected …”
Section: Discussionmentioning
confidence: 94%
“…Few Australian studies have examined the delays associated with interhospital transfer. A 2015 study of general surgical patients at a rural Victorian hospital found that a median 9.3 h elapsed between decision and execution of interhospital transfer . A primary reason for delay was lack of bed availability in the receiving hospital .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of IHDs of 36·8 per cent in the present study was similar to that in an earlier study at a well staffed teaching hospital in Nigeria, where 50 per cent of patients waited over 24 h, and 16 per cent waited more than 48 h for operative intervention. At a regional hospital in Uganda 48 per cent of 31 operations were delayed (median delay 14·8 h), and in the Ivory Coast 86 per cent of patients had a delay of more than 24 h from symptom onset to surgery, with more than 36 per cent waiting over 48 h. Delays were defined in the present study as longer than 24 h. Most surgeons would agree that this is too long to wait for emergency care, and several other studies, especially in LMICs, have used this definition, although some high‐income countries (HICs) have used shorter times. Future research to measure specific time intervals, including time to decision to operate, time to diagnostic studies and exact times to procedures, should clarify the length of an acceptable in‐hospital wait.…”
Section: Discussionmentioning
confidence: 85%